2018
DOI: 10.1101/396382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous viral elements are widespread in arthropod genomes and commonly give rise to piRNAs

Abstract: Arthropod genomes contain sequences derived from integrations of DNA and non-retroviral RNA viruses. These sequences, known as endogenous viral elements (EVEs), have been acquired over the course of evolution and have been proposed to serve as a record of past viral infection. Recent evidence indicates that EVEs can function as templates for the biogenesis of PIWI-interacting RNAs (piRNAs) in some mosquito species and cell lines, raising the possibility that EVEs may function as a source of immunological memor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…Recent studies have demonstrated the adaptive antiviral immunity in the mosquito A . aegyti [43] as well as many of other arthropods [44] suggesting likely involvement of piRNAs in facilitating TYLCV transmission by the vector whitefly B . tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the adaptive antiviral immunity in the mosquito A . aegyti [43] as well as many of other arthropods [44] suggesting likely involvement of piRNAs in facilitating TYLCV transmission by the vector whitefly B . tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…In principle, viruses of any Baltimore class can eventually become part of a host genome, although at highly different frequencies. [44][45][46][47][48] Retroviral elements are the most abundant class of endogenous viruses in vertebrates because of the mandatory genome integration step of their replication cycles. 49,50 The retroviral RNA is delivered to the cytoplasm, reverse-transcribed, and the dsDNA genome migrates into the nucleus via nuclear pores or during cell division.…”
Section: Mavirus In Comparison To Endogenous Viruses In Eukaryotesmentioning
confidence: 99%
“…Mavirus joins an illustrious list of endogenous virus elements (EVEs) found in eukaryotic genomes. In principle, viruses of any Baltimore class can eventually become part of a host genome, although at highly different frequencies …”
Section: Mavirus In Comparison To Endogenous Viruses In Eukaryotesmentioning
confidence: 99%
“…Additionally, large-scale sequence analysis has shown that many of these NIRVS cluster within piRNA producing genomic regions and produce primary piRNAs (Whitfield et al. 2017; Ter Horst et al 2018). This suggests that NIRVS have a functional role, perhaps involving the piRNA pathway.…”
Section: Introductionmentioning
confidence: 99%